Perceived HRM and turnover intentions of elderly care workers: perspective from person-job fit and institutional ownership - Fang Wu; Wei Chen; Ruyi Wan; Jiatong Lu; Qianqian Yu; Qilei Tu (BMC, 2024)
Abstract Background Although the phenomenon of high turnover rate in the elderly care industry has existed for a long time, there are few studies that have constructed frameworks to comprehensively analyze the strength of the effects of various factors on the turnover intention of elderly care workers.. This study analyzed the impact of different types of perceived human resource management practices on elderly care workers' turnover intentions and whether this relationship is moderated by person-job fit and ownership of elderly care institutions. Methods This is a cross-sectional and regional survey study. The study included questionnaire survey data from a total of 305 elderly care workers from 42 elderly care institutions in 21 provinces in China during June to September 2021. Descriptive statistics, Pearson correlation coefficient, multiple regression, and heterogeneity analyses were performed. Results Perceived work environment ( $$β$$ β =-0.5164, p< 0.01), perceived occupational protection ( $$β$$ β =-0.3390, p< 0.01), perceived welfare benefits ( $$β$$ β = -0.2620, p< 0.01) and perceived competency training ( $$β$$ β = -0.1421, p< 0.1) were all significantly and negatively related to turnover intentions, the quality of perceived work environment has the greatest impact on elderly care workers' turnover intentions. Under the moderating effects of person-job fit and ownership of elderly care institutions, there existed heterogeneity between perceived human resource management and turnover intentions among elderly care workers. High level of person-job fit and elderly care institutions' public feature can effectively weaken the negative impact of each type of perceived human resource management on turnover intention among elderly care workers. Conclusions The managers of elderly care institutions should optimize the management mechanism, typically pay attention to elderly care workers' working environment, formulate and improve the professional standards and job requirements for elderly care workers, promote the public welfare value of nursing care services, and strengthen the sense of honor and responsibility of elderly care workers to reduce the turnover rate.